Development of VR-Based Virtual Tours for South Sorong Regency Using the Analysis, Design, Development, Implementation, and Evaluation Model - Nur Miswar; Fitriyani Tella; Adrians Marthinus Demi Isir (Universitas Negeri Semarang, 2026)
Purpose: The limited availability of digital documentation and interactive promotional media has reduced public awareness of tourism destinations in South Sorong Regency. This study aims to develop and evaluate a Virtual Reality (VR)-based virtual tour as a solution to enhance user understanding, engagement, and visitation intention. Methods: This study employed a Research and Development approach using the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. Three tourism destinations were captured using 360° panoramic video and integrated into an interactive VR-based virtual tour. The virtual tour was evaluated with 97 respondents. Respondents completed a pre-test before using the virtual tour and a post-test after the experience to measure changes in understanding and interest, analyzed using the N-Gain method. Usability and acceptance were assessed through Likert-scale user questionnaires and percentage-based feasibility analysis. Media and material experts evaluated technical quality and content accuracy; their feedback was used for virtual tour media revision before final validation. Results: The results show improved user understanding and engagement, indicated by an N-Gain score of 0.64, categorized as moderate to high effectiveness. User evaluation yielded a feasibility score of 93%. Expert validation confirmed readiness, with feasibility scores of 89% from media experts and 94% from material experts. Novelty: This study introduces a systematic ADDIE-based engineering framework for multi-destination VR virtual tour development, integrating effectiveness analysis, usability evaluation, and expert validation as a scalable informatics solution for digital tourism promotion in underdeveloped regions.